Isolation and production of nanocrystalline cellulose from conocarpus fiber - Anish Khan; Mohammad Jawaid; Lau, Kia Kian; Parwaz Khan, Aftab Aslam; M. Asiri, Abdullah (MDPI, 2021)
Conocarpus fiber is a lignocellulosic biomass rich in cellulose potentially used for producing nanocrystalline cellulose (NCC), a biomaterial extensively employed in various application fields. In the present work, different hydrolysis times of 10, 20 and 30 min were applied to chemically pre-treated Conocarpus fiber to produce CPNC1, CPNC2, and CPNC3 particles. With acid hydrolysis treatment, the yield of NCC product was successfully retained at 17–19%. Individual, rod-like shapes of NCC particles could be clearly observed under microscopy examination. From chemical composition analysis, a relatively pure cellulose compartment was produced for all NCC samples with substantial removal of lignin and hemicellulose. The physicochemical analysis proved that each nanoparticle sample possessed strong cellulose crystalline structure. For thermal analyses, the heat resistance of NCCs was gradually enhanced with the increased hydrolysis times. Therefore, the extracted NCC product from Conocarpus fiber could be a green nano-filler for developing nanocomposite material in the future.